Sharia Compliance Implementation on Gold Pawn Products at Sharia Pawnshops and Sharia Banks XYZ - Nova Purnama Sari; Ruslan Abdul Ghofur; Khumaidi Ja'far; Surono , (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2021)
Sharia compliance (sharia compliance) in the gold pawn business in the current era tends to be often violated by sharia companies in order to get greater profits. Even though interest in Islamic gold pawns continues to increase. On the other hand, the shariah compliance component is the main differentiator between sharia companies and conventional companies. Therefore, this study aims to analyze how the implementation of shariah compliance on gold pawn products is applied to Sharia Pawnshops and Mandiri Syariah Banks in Metro City, Lampung. The research was conducted in 2019 at the Syariah Pawnshop and Mandiri Syariah Bank in Metro City. The research method used is a case study in both sharia companies, with a qualitative descriptive analysis method by comparing the implementation of the gold pawn in the two sharia companies with the MUI fatwa and six shariah compliance indicators that the calculation formula does not purely use the loan amount as a cost determination, but only uses presentation only. While the administrative costs are different for each group, the Sharia Pawnshop will provide discounts for customers who do not borrow in full on the estimated pawned goods. Then the administrative costs at Bank Syariah Mandiri have details that are in accordance with the costs that are clearly needed, namely 2 stamps and 0.133% of the loan value